Payoff Shares in Two-Player Contests - Samuel Häfner; Georg Nöldeke (University of Basel, Center of Business and Economics (WWZ), 2014)
In contest models with symmetric valuations, equilibrium payoffs are positive shares of the value of the prize. In contrast to a bargaining situation, these shares sum to less than one because a share of the value is lost due to rent-dissipation. We ask: can every such division into payoff shares arise as the outcome of the unique pure-strategy Nash equilibrium of a simple asymmetric contest in which contestants differ in the effectiveness of their efforts? For two-player contests the answer is shown to be positive.
Keywords: C72; D72; D74; 330; Contests; Pure-Strategy Equilibrium; Rent-Dissipation